Differential neutrophil activation in viral infections: Enhanced TLR‐7/8‐mediated CXCL8 release in asthma. Issue 1 (18th October 2015) - Tang, Francesca S.M.; Van Ly, David; Spann, Kirsten; Reading, Patrick C.; Burgess, Janette K.; Hartl, Dominik; Baines, Katherine J.; Oliver, Brian G.
Abstract: Background and objective: Respiratory viral infections are a major cause of asthma exacerbations. Neutrophils accumulate in the airways and the mechanisms that link neutrophilic inflammation, viral infections and exacerbations are unclear. This study aims to investigate anti‐viral responses in neutrophils from patients with and without asthma and to investigate if neutrophils can be directly activated by respiratory viruses. Methods: Neutrophils from peripheral blood from asthmatic and non‐asthmatic individuals were isolated and stimulated with lipopolysaccharide (LPS) (1 μg/mL), f‐met‐leu‐phe (fMLP) (100 nM), imiquimod (3 μg/mL), R848 (1.5 μg/mL), poly I:C (10 μg/mL), RV16 (multiplicity of infection (MOI)1), respiratory syncytial virus (RSV) (MOI1) or influenza virus (MOI1). Cell‐free supernatants were collected after 1 h of neutrophil elastase (NE) and matrix metalloproteinase (MMP)‐9 release, or after 24 h for CXCL8 release. Results: LPS, fMLP, imiquimod and R848 stimulated the release of CXCL8, NE and MMP‐9 whereas poly I:C selectively induced CXCL8 release only. R848‐induced CXCL8 release was enhanced in neutrophils from asthmatics compared with non‐asthmatic cells ( P  < 0.01). RSV triggered the release of CXCL8 and NE from neutrophils, whereas RV16 or influenza had no effect. Conclusion: Neutrophils release CXCL8, NE and MMP‐9 in response to viral surrogates with R848‐induced CXCL8 release being specifically enhanced in asthmatic neutrophils. Toll‐like receptor (TLR7/8) dysregulation may play a role in neutrophilic inflammation in viral‐induced exacerbations. Abstract : We aimed to investigate and compare neutrophil responses to bacterial compounds and viral mimetics as well as compare responses between people with and without asthma. We also investigated neutrophil responses to live respiratory viruses. Here we provide a novel comprehensive comparison showing differential and specific activation in innate immune cells. See Editorial, page 10